2001
DOI: 10.1016/s0009-3084(00)00203-6
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic investigation of the morphology and calcium-induced fusion of lipid vesicles with an oligomerised inner leaflet

Abstract: The lipid head groups in the inner leaflet of unilamellar bilayer vesicles of the synthetic lipids DHPBNS and DDPBNS can be selectively oligomerised. Earlier studies have established that these vesicles fuse much slower and less extensively upon oligomerisation of the lipid head groups. The morphology and calcium-induced fusion of vesicles of DHPBNS and DDPBNS were investigated using cryo-electron microscopy. DHPBNS vesicles are not spherical but flattened, ellipsoidal structures. Upon addition of CaCl(2), DHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…It is possible that the solvent evaporation process employed during sample preparation destabilized the vesicles, and exposed the interior of the vesicles to the staining agent. Similar observations were also reported for bilayer vesicles formed from synthetic lipids 1,2‐di‐ n ‐hexadecyloxypropyl‐4‐(beta‐nitrostyryl) phosphate (DHPBNS) under aqueous conditions . Some large particles with d ≈ 300–400 nm were also observed, which were likely generated via fusion of smaller particles during solvent evaporation (indicated by arrows in Figure a).…”
Section: Resultssupporting
confidence: 80%
“…It is possible that the solvent evaporation process employed during sample preparation destabilized the vesicles, and exposed the interior of the vesicles to the staining agent. Similar observations were also reported for bilayer vesicles formed from synthetic lipids 1,2‐di‐ n ‐hexadecyloxypropyl‐4‐(beta‐nitrostyryl) phosphate (DHPBNS) under aqueous conditions . Some large particles with d ≈ 300–400 nm were also observed, which were likely generated via fusion of smaller particles during solvent evaporation (indicated by arrows in Figure a).…”
Section: Resultssupporting
confidence: 80%
“…The most interesting difference between mixed and plain arsonoliposomes in terms of Ca 2+ ‐induced vesicle aggregation is that, in all cases of mixed arsonoliposomes (even the DSPC‐containing ones), this aggregation is not EDTA‐reversible, a fact that indicates that fusion is the mechanism of increase of vesicle size. This indication was confirmed after morphological evaluation of the effect of calcium on the mixed arsonoliposomes which revealed that vesicles are fusing into larger vesicles, possibly by the previously reported21–24 “stalk‐pore” model. Concluding, we should mention that this last finding may suggest that, when arsonolipids are incorporated in liposomal membranes with phospholipids, they may enhance the possibility of fusion between vesicles and cells, depending on the composition of the specific cell membrane.…”
Section: Discussionsupporting
confidence: 74%
“…As mentioned above, the effect of EDTA on turbidity of vesicle dispersions that have been aggregated by Ca 2+ ions may provide some insight on the aggregation mechanism 21. For this, we added EDTA (in a tenfold molar excess) in the aggregated samples and remeasured their turbidity.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst the formation and the structure of single-and multi-bilayer liposomes is common knowledge, it is less widely known that in aqueous systems lipid and lipid mixtures also form other variously shaped particles, in particular sheets, elongated twisted ribbons and helical fibres (Archibald and Mann, 1993;Goldstein et al, 1997;Ravoo et al, 2001). In cholesterol-containing model bile systems used for investigating cholesterol crystallization, evidence has been presented for the presence of helical ribbons (Khaykovich et al, 2007;Komura and Zhong-can 1998).…”
Section: Introductionmentioning
confidence: 99%